Bridging the intention-behavior gap for cardiac rehabilitation participation: the role of perceived barriers - Williamson, Tamara M.; Rouleau, Codie R.; Aggarwal, Sandeep G.; Arena, Ross; Campbell, Tavis S. (Disability and rehabilitation, 2020)
Purpose: Patients referred to cardiac rehabilitation after an acute coronary syndrome event commonly report strong intention to attend, but at least one-third do not participate. This study explored whether well-documented cardiac rehabilitation barriers (e.g., comorbidities, logistical/time constraints, and low social support) moderate the association between intention to participate and actual program enrollment and attendance. Method: Following referral but prior to commencing a 12-week outpatient cardiac rehabilitation program, 100 patients with acute coronary syndrome completed measures of intention to attend cardiac rehabilitation, perceived cardiac rehabilitation barriers, and social support. Program enrollment and attendance were determined by chart review. Results: Despite high reported intention to attend (M = 6.08/7.00, SD = 1.80), nearly one-in-five did not enroll. Weaker intention to attend (b = 0.46, SE = 0.16, p = 0.004) and greater cardiac rehabilitation barriers (b= −1.67, SE = 0.70, p = 0.017) corresponded to lower program enrollment. Similarly, weaker intention (b = 2.29, SE = 0.50, p < 0.001) and greater barriers (b =−6.19, SE = 1.55, p < 0.001) predicted poorer attendance. Barriers moderated the association between intention to participate and cardiac rehabilitation enrollment (b=−0.60, SE = 0.29, p = 0.037) and attendance (b = −3.12, SE = 1.02, p = 0.003). Conclusions: Perceived cardiac rehabilitation barriers influence whether patients successfully translate their intention to attend into actual program participation. Enhancing self-efficacy to overcome barriers may represent an important intervention target among prospective cardiac rehabilitation patients. Implications for Rehabilitation Patients with acute coronary syndrome report strong intention to attend cardiac rehabilitation upon referral, yet cardiac rehabilitation programs remain underutilized. Assessing and addressing perceived barriers during the transition to cardiac rehabilitation, even when patients present as highly motivated to attend, may be critical to promoting program uptake. Rehabilitation professionals should ask patients about specific barriers to attending cardiac rehabilitation (e.g., financial constraints, transportation problems) and provide individualized solutions (e.g., fee subsidization, home- or web-based programs) to increase participation.